A stress-driven local-nonlocal mixture model for Timoshenko nano-beams. (1st May 2019) - Barretta, Raffaele; Caporale, Andrea; Faghidian, S. Ali; Luciano, Raimondo; Marotti de Sciarra, Francesco; Medaglia, Carlo Maria
Abstract: A well-posed stress-driven mixture is proposed for Timoshenko nano-beams. The model is a convex combination of local and nonlocal phases and circumvents some problems of ill-posedness emerged in strain-driven Eringen-like formulations for structures of nanotechnological interest. The nonlocal part of the mixture is the integral convolution between stress field and a bi-exponential averaging kernel function characterized by a scale parameter. The stress-driven mixture is equivalent to a differential problem equipped with constitutive boundary conditions involving bending and shear fields. Closed-form solutions of Timoshenko nano-beams for selected boundary and loading conditions are established by an effective analytical strategy. The numerical results exhibit a stiffening behavior in terms of scale parameter.